2018
DOI: 10.4236/jdm.2018.84013
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Pre-Diabetes among Adults in an Urban Slum in South East Nigeria

Abstract: Background: Despite the rising prevalence of diabetes in Nigeria and sub-Saharan Africa, few studies have assessed the prevalence of prediabetes and diabetes in people with low socioeconomic status or urban slums. Methods: Using the WHO STEP-wise approach to surveillance of noncommunicable diseases, we estimated the prevalence of diabetes and prediabetes among adults 20 years and older living in two urban slums in Enugu south east Nigeria. Diabetes was defined as previous history of diabetes, use of hypoglycem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Diabetes is a common non-communicable disorder in South East Nigeria with a current prevalence as high as 11% [1]. Diabetes in the country presents a rising public health challenge [2] [3] [4] and many cases are probably undetected [1] [2] [3]. Poor glycemic control is a risk factor for both micro and macro vascular complications of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a common non-communicable disorder in South East Nigeria with a current prevalence as high as 11% [1]. Diabetes in the country presents a rising public health challenge [2] [3] [4] and many cases are probably undetected [1] [2] [3]. Poor glycemic control is a risk factor for both micro and macro vascular complications of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies by Osuntokun et al [12] [13] found a community prevalence of 58 -400/100,000, a crude annual mortality rate of about 700/100,000 per year and age specific mortality in the elderly of about 100/100,000 per year while more recent studies have reported higher rates [17] [18]. The increasing prevalence of stroke is clearly related to increasing rates of cardiovascular and metabolic disorders which were rare in the early and middle decades of the last century [20] [21] [22] [28] [29].…”
Section: Discussionmentioning
confidence: 99%
“…These substances were not significant risk for stroke in the index study probably because we surveyed the rates of current use rate than lifetime use of these substances. The prevalences of hypertension and diabetes in the index communities have been previously documented [21] [22]. The overlapping impact of low socio-economic status and these factors may contribute to high rates of stroke severity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full description of the study protocol had been documented previously [25]. The inhabitants were surveyed over a 4-week period (August 12-September 9, 2013).…”
Section: Methodsmentioning
confidence: 99%